Search for a quantum critical point in CeRhSi3 via electrical resistivity - Iida, Hiroki; Sugawara, Tetsuya; Aoki, Haruyoshi; Kimura, Noriaki (physica status solidi (b), 2013)
We have verified an existence of a quantum critical point (QCP) in heavy‐fermion superconductor CeRhSi3 under magnetic fields and pressures by using the electrical resistivity measurements. Firstly, we revealed magnetic field–temperature (H–T) phase diagrams at several pressures: below and above the pressure where the antiferromagnetic (AFM) order disappears in zero magnetic field. In a higher pressure, we determined the quantum‐phase‐transition field HM where the AFM transition temperature drops to zero. Recovery to Fermi liquid state is not clearly observed above HM. Therefore, HM is not conclusively determined as the QCP.